Empirical study: the urgency of extraterritorial principles in business competition law in Indonesia - Chandra Setiawan; Fennieka Kristianto; Perina Amelia; Dania Sabrina; Andryan Maju Kevin Martin Purba; Kezia Sharon Christabella; Nadya Nadya; Reygita Yusiani (Jurnal Indovisi, 2025)
Today's fast-paced economy makes business transactions seamless and seamless. Transactions are no longer only local, but also spread across countries. The economic system in this modern era 'obliges' a country to be able to properly apply business competition law. One of the functions of business competition law is as a means of controlling the abuse of economic power by business actors by preventing monopolistic practices and unfair business competition. Meanwhile, in Law no. 5/1999, the ICC has no extraterritorial powers. The research method used in this research is normative juridical by making Law No. 5 Year 1999 as the object of study.